Analisis Kinerja Crusher Pada Kegiatan Produksi Batu Gamping Berdasarkan Efisiensi Biaya Operasional Untuk Mencapai Target Produksi PT. Sumbar Calcium Pratama, Kecamatan Lareh Sago Halaban, Kabupaten Lima Puluh Kota - Indah Suryani; Rizto Salia Zakri (Journals Mining Engineering : Bina Tambang, 2022)
Abstract. PT. Sumbar Calcium Pratama is a company engaged in the limestone mining business. In its mining activities, PT. Sumbar Calcium Pratama focuses more on processing activities in the form of reducing limestone using a crusher crusher, this activity uses 3 crusher units with a production target of each crusher A 2.5 tons/hour, crusher B 2.5 tons/hour, and crusher C 5 tons/hour so that the total production is 1750 tons/month. In October PT. Sumbar Calcium Pratama is only able to produce a production of 1,302 tons/month this is due to the non-optimal use of the crusher, it is necessary to calculate the productivity of the tool so that it can be optimized according to the working hours that have been set so that there is no excess financing. The purpose of this study is to determine operational costs in limestone processing, and knowing the value of crusher efficiency.From the calculation results, the cost of crusher A is 130,167/ton, crusher B 156,919/ton, and crusher C 174,179/ton. After being analyzed for calcium carbonate production, the planned production targets are crusher A 119.742/ton, crusher B 151.213/ton, and crusher C 155.064/tonKeywords:  production, operational costs, work efficiency